2020
DOI: 10.3390/pathogens9070593
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Mycoplasma bovis Diversity and Antimicrobial Susceptibility in Calf Feedlots Undergoing a Respiratory Disease Outbreak

Abstract: Bovine respiratory diseases (BRD) are widespread in veal calf feedlots. Several pathogens are implicated, both viruses and bacteria, one of which, Mycoplasma bovis, is under-researched. This worldwide-distributed bacterium has been shown to be highly resistant in vitro to the main antimicrobials used to treat BRD. Our objective was to monitor the relative prevalence of M. bovis during BRD episodes, its diversity, and its resistance phenotype in relation to antimicrobial use. For this purpose, a two-year longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
(64 reference statements)
2
25
0
Order By: Relevance
“…However, because some clinical signs, age classes or production types are dominant in Vigimyc-sampled animals ( Table 1 ), they are also dominant in the AST panel. We remain alert with respect to a potential bias and for M. bovis we have already shown the absence of influence of (i) tissue tropism ( 17 ), or (ii) sampling time post antimicrobial therapy ( 23 ) on AMR.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, because some clinical signs, age classes or production types are dominant in Vigimyc-sampled animals ( Table 1 ), they are also dominant in the AST panel. We remain alert with respect to a potential bias and for M. bovis we have already shown the absence of influence of (i) tissue tropism ( 17 ), or (ii) sampling time post antimicrobial therapy ( 23 ) on AMR.…”
Section: Resultsmentioning
confidence: 98%
“…Between 2014 and 2019, the preservation rate allowed a first-line conservation of 414 cultures out of 465 identified per year on average (Table 1). After several quality controls, isolates derived from these cultures have regularly been included in various studies on epidemiology [see for example (23)], method validation (24) or mycoplasma biology (25). In the last decade, this collection has also been a valuable source of material for studying the AMR of French isolates over time (15)(16)(17)22).…”
Section: Clinicoepidemiological Trends From the Vigimyc Network Over The 2014-2019 Periodmentioning
confidence: 99%
“…For instance, polC subtyping was insufficiently discriminatory for recent isolates, generating only two subtypes, with the majority of isolates assigned to st3, while st2 isolates appeared restricted to France or the Netherlands. In France, st2 is currently the main clone in the circulation, with st3 constituting a maximum of 20% of the M. bovis population to date [38]. The st2 and st3 subtypes were further subdivided into 16 subtypes by MLST-1a [26] (Table S1), indicating that MLSTs better inform international epidemiological trends.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a decrease in the antimicrobial susceptibility of M. bovis to various antimicrobial classes targeting protein synthesis (e.g., phenicols, tetracyclines, lincosamides and macrolides) and DNA synthesis (e.g., fluoroquinolones) has been reported in different countries [ 4 , 5 , 6 , 7 , 8 , 9 ]. Especially for macrolides, high percentages of resistant M. bovis isolates are reported, while fluoroquinolones remain the most effective antimicrobial in vitro in most countries [ 5 , 9 , 10 , 11 ], except for Spain and Italy [ 6 , 7 ]. Geographical differences in the antimicrobial susceptibility of M. bovis, as well as differences between strains isolated from various predilection sites, such as the joint, udder and lung, have been described [ 5 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…If production-specific antimicrobial susceptibility exists for M. bovis , it might be necessary to adjust M. bovis treatment guidelines to specific production systems. Additionally, whether antimicrobial resistance is associated with specific genetic strains is not clear, as some studies observed no association between genetic subtypes based on the polC subtyping scheme [ 11 ], while others did for lincosamides and macrolides [ 9 ]. With whole genome sequencing (WGS) becoming more popular and commercially available for identification and strain typing [ 16 , 17 , 18 , 19 ], it might be helpful to determine whether phenotypic antimicrobial susceptibility patterns are associated with genomic clusters of M. bovis .…”
Section: Introductionmentioning
confidence: 99%